Kemampuan Diversifikasi Pendapatan dan Keberlanjutan Keuangan UMKM Kuliner: Peran Mediasi Stabilitas Pendapatan - Nur Listiani; Siti Alliyah; Rita Meiriyanti (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study aims to examine the effect of revenue diversification capability on the financial sustainability of culinary micro, small, and medium enterprises (MSMEs), with income stability as a mediating variable. Data were collected through a survey of 150 culinary MSMEs in Rembang Regency, Central Java, Indonesia, using a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a bootstrapping approach to test the proposed relationships. The results indicate that revenue diversification capability has a positive and significant effect on both income stability and financial sustainability. Income stability also significantly influences financial sustainability and partially mediates the relationship between diversification capability and sustainability. These findings suggest that diversification enhances financial sustainability primarily by stabilizing income streams, providing practical implications for MSMEs to develop strategies that ensure more predictable and sustainable income.